The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1200/jco.2009.24.1968
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Biopsy During Prostate Cancer Screening Using a Four-Kallikrein Panel: An Independent Replication

Abstract: PurposeWe previously reported that a panel of four kallikrein forms in blood—total, free, and intact prostate-specific antigen (PSA) and kallikrein-related peptidase 2 (hK2)—can reduce unnecessary biopsy in previously unscreened men with elevated total PSA. We aimed to replicate our findings in a large, independent, representative, population-based cohort.Patients and MethodsThe study cohort included 2,914 previously unscreened men undergoing biopsy as a result of elevated PSA (≥ 3 ng/mL) in the European Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
161
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 17 publications
(14 reference statements)
9
161
0
1
Order By: Relevance
“…A panel of four serum kallikreins (total PSA, free PSA, intact PSA, and human kallikrein protein 2 (hK2) has received extensive evaluation in the pre-biopsy setting and is commercially marketed as the 4Kscore Test (4K, OPKO Lab, Nashville, TN) [19][20][21][22][23]24•]. The algorithm representing these components was initially derived from data based on participants within the European Randomized Study of Prostate Cancer Screening (ERSPC) and Prostate Testing for Cancer and Treatment (ProtecT) studies.…”
Section: Emerging Serum Biomarkersmentioning
confidence: 99%
“…A panel of four serum kallikreins (total PSA, free PSA, intact PSA, and human kallikrein protein 2 (hK2) has received extensive evaluation in the pre-biopsy setting and is commercially marketed as the 4Kscore Test (4K, OPKO Lab, Nashville, TN) [19][20][21][22][23]24•]. The algorithm representing these components was initially derived from data based on participants within the European Randomized Study of Prostate Cancer Screening (ERSPC) and Prostate Testing for Cancer and Treatment (ProtecT) studies.…”
Section: Emerging Serum Biomarkersmentioning
confidence: 99%
“…Vickers and colleagues used four serum kallikrein markers, including total PSA, free PSA, intact PSA, and kallikrein-related peptidase 2 to develop a statistical model to predict prostate biopsy results [81]. This model was successful in predicting the biopsy results in men with elevated PSA, suggesting that biopsy rates could be significantly reduced, while a relatively few men with elevated PSA levels and cancer would be advised not to undergo biopsy, most of whom would have low-grade disease [82].…”
Section: Future Directionsmentioning
confidence: 99%
“…Overtreatment is a major problem in patients with early prostate cancer, resulting not only in unnecessary biopsies, but also in treatment being instituted in patients with indolent early prostate cancer, especially the elderly, who may be more threatened by the side effects of therapy rather than by the disease itself. It has been demonstrated that utilization of a panel of biomarkers that includes PSA forms and KLK2 could result in the reduction of biopsy rates (19) .…”
Section: Bohuslav Melicharmentioning
confidence: 99%